SCIENTIFIC APPROACH AND STUDENT-CENTERED LEARNING IN ELT: A SYSTEMATIC LITERATURE REVIEW OF INDONESIAN RESEARCH (2013–2025) - Kaharap, Mongga; Perdana, Indra; Karani, Elanneri (Journal Compound: Improving the Quality of English Education, 2025)
The integration of the scientific approach into English Language Teaching (ELT) has played a transformative role in Indonesian education since the implementation of the 2013 Curriculum. This systematic literature review explores how the scientific approach aligns with student-centered learning principles and its pedagogical implications in the Indonesian ELT context from 2013 to 2025. A total of 52 peer-reviewed journal articles indexed in SINTA 1 to 3 and international databases were analyzed using the PRISMA model. The review focuses on the pedagogical strategies, learning outcomes, teacher readiness, and classroom practices associated with the scientific approach. Findings indicate that the scientific approach supports learner autonomy, critical thinking, and communicative competence when implemented with contextual sensitivity and adequate teacher training. However, various challenges persist, including misalignment in assessment, limited resources, and superficial understanding of scientific stages. The paper provides implications for curriculum designers, teacher educators, and policymakers to strengthen scientific pedagogy in Indonesian ELT